2013
DOI: 10.1007/s11356-013-2047-5
|View full text |Cite
|
Sign up to set email alerts
|

Field controlled experiments on the physiological responses of maize (Zea mays L.) leaves to low-level air and soil mercury exposures

Abstract: Thousands of tons of mercury (Hg) are released from anthropogenic and natural sources to the atmosphere in a gaseous elemental form per year, yet little is known regarding the influence of airborne Hg on the physiological activities of plant leaves. In the present study, the effects of low-level air and soil Hg exposures on the gas exchange parameters of maize (Zea mays L.) leaves and their accumulation of Hg, proline, and malondialdehyde (MDA) were examined via field open-top chamber and Hg-enriched soil expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Hg pollution has aroused global concern because of its toxicity to organisms, persistence in the environment and long-range transport [25] . In some contaminated areas, food chain transfer is very common [31] [34] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hg pollution has aroused global concern because of its toxicity to organisms, persistence in the environment and long-range transport [25] . In some contaminated areas, food chain transfer is very common [31] [34] .…”
Section: Discussionmentioning
confidence: 99%
“…In maize, there have been some studies on the physiological and biochemical responses to Hg tolerance. The net photosynthesis rate and carboxylation efficiency of maize leaves exposed to 50 ng m −3 Hg (in the air) were significantly reduced [25] . In vivo , HgCl 2 inhibited 5-aminolevulinic acid dehydratase activity in excised greening leaf segments of maize, and the inhibition could be alleviated by the addition of KNO 3 [26] .…”
Section: Introductionmentioning
confidence: 95%
“…The study of Niu et al (2011) focusing on wheat and corn indicated a significant correlation between foliage Hg content and the exposure level of airborne Hg 0 for their principal growing stages. In a further study, Niu et al (2014) showed that only a moderate level of Hg 0 pollution in air (∼ 20 ng m −3 ) was required to induce measurable physiological stress on corn tissue.…”
Section: Introductionmentioning
confidence: 94%
“…In this research, the absorption and accumulation of heavy metal ion Hg 2+ led to the drop in Pn of wheat seedlings to some extent at different times. Meanwhile, the accumulation of Hg 2+ also brought about relatively large magnitudes of Tr fluctuation, because the root systems of plants exerted certain inhibitive effects on the uptake of heavy metal ions (Niu et al, 2013), which partly resulted in the enhancement of Pn and Tr values in wheat seedlings (Figs. 2 and 3).…”
Section: Discussionmentioning
confidence: 99%